Assessment of Fence Systems Usiing Fuzzy Modeliing - Hadacek, Libor; Lovecek, Tomas; Scurek, Radomir; Zeegers, Mikael H. L. (Communications - Scientific Letters of the University of Zilina, 2015)
The article deals with the use of fuzzy modeling for time estimate of wire fence systems resistance. The resulting time can be used then in quantitative analytical methods for assessing the effectiveness of a technical protection system. The values of the fence system time resistance are very difficult to detect. Neither the technical standards give an exhaustive answer to questions related to time resistance of mechanical barriers. Some experiments were carried out with the aim to determine the time required for penetration of the selected wire fence obstacles. On the basis of the experiment results fuzzy rules were designed allowing, in conjunction with a suitable software tool, precise estimation of the wire fence barriers time resistance.
Keywords: fuzzy modeling; fence system; resistance; perimeter protection